Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1182/blood.v98.1.85
|View full text |Cite
|
Sign up to set email alerts
|

Platelet characteristics in patients with X-linked macrothrombocytopenia because of a novel GATA1mutation

Abstract: A new mutation is described in the Xlinked gene GATA1, resulting in macrothrombocytopenia and mild dyserythropoietic features but no marked anemia in a 4-generation family. The molecular basis for the observed phenotype is a substitution of glycine for aspartate in the strictly conserved codon 218 (D218G) of the amino-terminal zinc finger loop of the transcription factor GATA1. Zinc finger interaction studies demonstrated that this mutation results in a weak loss of affinity of GATA1 for its essential cofactor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
204
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 226 publications
(212 citation statements)
references
References 29 publications
7
204
1
Order By: Relevance
“…12 Other amino-terminal zinc finger mutations affect cofactor binding and cause thrombocytopenia and dyserythropoiesis. [13][14][15][16] While we do not know that any of these cofactor binding face mutations result in a definitive gray platelet phenotype, these mutations do result in macrothrombocytopenia and/or ␣-granule deficiency. Therefore, we suggest that GATA1 mutations should be considered in seemingly sporadic, male cases of GPS.…”
Section: Resultsmentioning
confidence: 99%
“…12 Other amino-terminal zinc finger mutations affect cofactor binding and cause thrombocytopenia and dyserythropoiesis. [13][14][15][16] While we do not know that any of these cofactor binding face mutations result in a definitive gray platelet phenotype, these mutations do result in macrothrombocytopenia and/or ␣-granule deficiency. Therefore, we suggest that GATA1 mutations should be considered in seemingly sporadic, male cases of GPS.…”
Section: Resultsmentioning
confidence: 99%
“…Vertebrate GATA-1 and Runx1 are coexpressed and have overlapping functions during hematopoiesis, including megakaryopoiesis (15)(16)(17)(18)(19)(20)(21)(22). In addition, in vitro studies have suggested that the GATA-1:Runx1 complex directs megakaryocyte differentiation (22).…”
Section: Srp and Lz Synergistically Activate The Crystal Cell Programmentioning
confidence: 99%
“…For instance, somatic mutations in the GATA1 gene, which result in the production of GATA1-⌬NT (or GATA1s), are a prerequisite for the onset of transient myeloproliferative disorder (TMD) and subsequent acute megakaryoblastic leukemia (AMkL) in Down syndrome patients (44). Similarly, GATA1 mutations in the N-finger domain were found in multiple cases with familial anemia and thrombocytopenia (45)(46)(47)(48). In the latter cases, the association potential of GATA1 with either FOG1 or GATAbox DNA was attenuated, indicating that the N-finger domain is important for the GATA1 activity.…”
Section: Discussionmentioning
confidence: 99%